Sustained release of chlorogenic acid-loaded nanomicelles alleviates bone loss in mouse periodontitis. (17th August 2022) - Li, Han; Xu, Jiming; Hu, Jun-Feng; Hu, Qing-Yun; Fang, Xiaolin; Sun, Zhi-Jun; Xu, Zhigang; Zhang, Lu
Abstract : Schematic of the preparation of chlorogenic acid (CGA)-loaded poly(d, l -lactide- co -glycolide) (PLGA) nanomicelles using polyvinylpyrrolidone (PVP)-modified nanomicelles (CGA–PLGA@PVP), and assessment of their effects in the treatment of mouse periodontitis. Abstract : Periodontitis is a prevalent chronic inflammatory disease that destroys the periodontal supporting tissues, impinges on oral health, and is correlated with an increased risk of systemic disease. Currently, the main drug treatment is antibiotic therapy; however, systemic antibiotic therapy still has various drawbacks such as bacterial resistance, low bioavailability and burst release. It is noteworthy that the local use of non-antibiotic drugs with sustained release characteristics can effectively overcome these problems. It has been documented that chlorogenic acid (CGA) has good anti-inflammatory and antioxidant properties. To achieve the sustained release of CGA, we synthesized CGA–PLGA@PVP nanomicelles by loading CGA onto poly(d, l -lactide- co -glycolide) (PLGA) and modified them with polyvinylpyrrolidone (PVP) for better dispersion. The results demonstrated that CGA–PLGA@PVP nanomicelles could prolong the release time of CGA, and could not only effectively remove reactive oxygen species (ROS) but also downregulate the overexpression of proinflammatory cytokines in lipopolysaccharide (LPS)-treated RAW264.7 cells. Moreover, CGA–PLGA@PVP nanomicelles could remain in gingival tissue for more than 24 hours after local injection, inhibit alveolar bone resorption and prevent the progression of periodontitis in a mouse model, showing good biocompatibility. Therefore, CGA–PLGA@PVP nanomicelles have great properties and are expected to be a novel therapeutic strategy for periodontitis.